Can domestic medical tourism contribute to healthcare equity? A commentary - Michelle Rydback; Akmal Hyder; Gloria Macassa; Clara Simonsson (Taylor & Francis Group, 2022)
Pupose - This essay uses service marketing concept to discuss how domestic medical tourism (DMT) can contribute to healthcare equity in developed countries.Approach - The authors take up several vital issues. First, the potential benefits of DMT are outlined from a healthcare equity perspective; second, the challenges that DMT confronts in reaching its aim are identified; and finally, a few research areas are suggested.Finding - It is suggested that increased awareness about the healthcare service and proper service delivery are required to improve healthcare equity.Practical implication - This paper raises several research issues from service marketing to deal with delivery, communication, efficiency, and insurance practices regarding healthcare.Social implication - From a societal point of view, it explores how healthcare equity can be improved by DMT.